2012
DOI: 10.7314/apjcp.2012.13.3.1019
|View full text |Cite
|
Sign up to set email alerts
|

Type-Specific Incidence and Persistence of HPV Infection among Young Women: A Prospective Study in North India

Abstract: Background: Infections with human papillomavirus (HPV) are highly prevalent among sexually active young women in India. However, not much is known about the incidence of type-specific human papillomavirus (HPV) infections and their patterns of persistence, especially in the Indian context. Objective: The objective of this study was to evaluate the rate of acquisition and persistence of HPV types in young women. Methods: Women residing in an urban slum in Delhi (n=1300) were followed for 24 months at 6 monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
3
18
4
Order By: Relevance
“…Compared to other studies in India, the present study disclosed a high prevalence of HPV infection among the women with normal cytology showing minor gynecological complaint [5, 6, 1517]. This study, however, did not look for any bacterial, fungal or HIV infection which could make them prone to HPV infection in symptomatic cases.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Compared to other studies in India, the present study disclosed a high prevalence of HPV infection among the women with normal cytology showing minor gynecological complaint [5, 6, 1517]. This study, however, did not look for any bacterial, fungal or HIV infection which could make them prone to HPV infection in symptomatic cases.…”
Section: Discussioncontrasting
confidence: 79%
“…Though there are several reports showing the association of multiple infections with cervical cancer [39, 40] the biological effect of multiple infections on cervical diseases has not yet been established. Synergistic effect of multiple infections by HPV genotypes on carcinogenesis is supported by many studies [7–9, 17, 26], while contradicting studies [25, 29, 31, 32, 35] invoke confusion. Association of multiple infections with tumor size is an interesting finding in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern is observed in the most studies all over the world, although second peaks are sometimes observed in older women (Munoz et al, 2004;Franceschi et al, 2006;Trottier and Franco, 2006;Lee et al, 2012). This decrease in HPV infection prevalence with age may be explained by the fact in most cases HPV infection is self-limited and the virus is cleared by the host innate immune response (Ho et al, 1998;Stanley, 2006;Datta et al, 2012). In some cases the immune response fails to clear the infection and in subjects persistently infected by HR-HPV types there is a risk of progression to high-grade cervical intraepithelial neoplasia and invasive cancer (Ho et al, 1998;Schlecht et al, 2001;Snijders et al, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…The highest prevalence of the HR-HPV infection (55.0%) appeared in the >60 years group was more likely for viral persistence than for acquisition of new infection (Castle et al, 2005;Goodman et al, 2008). It was reported that the persistence rate of the HR-HPV infection was higher than LR-HPV infection, and it was a strong predictor for the development of CIN2/3 and invasive cervical cancer (Dalstein et al, 2003;Datta et al, 2012). The previous work found that the HR-HPV DNA was positive among 80% of patients with cervical cancer, so more inspections, including cytology and even colposcopy, should be proceed among women aged >60 years for the prevention of cervical cancer (Wang et al, 2013).…”
Section: Xiao-chuan Wang Et Almentioning
confidence: 99%